Instant biofeedback provided by wearable sensor technology can help to optimize exercise and prevent injury and overuse - Düking, P.; Holmberg, H. C.; Sperlich, B. (Frontiers in Physiology, 2017)
With great interest, we have been following the developing variety and popularity of commercially available wearable sensor technologies, as well as the discussion concerning their usefulness for improving fitness and health (Duking et al., 2016; Halson et al., 2016; Sperlich and Holmberg, 2016). Although many of these devices may not necessarily fulfill scientific criteria for quality (Sperlich and Holmberg, 2016) or may pose a threat to the security of personal data (Austen, 2015), we would like to emphasize here that many individuals who seek to improve their health or physical performance do so on their own, without the guidance of professionals to design their fitness training. Although professional guidance is, of course, important, such individuals and, especially beginners, would find instantaneous (bio)feedback beneficial for optimal adaptation and prevention of overuse or injury. We believe wearable sensor technologies, in conjunction with appropriate (mobile) applications, data mining and machine learning algorithms, can provide biofeedback that is useful in many ways.